Strategi Sinematografi dalam Membangun Emosi pada Video Feature: ‘Perempuan di Balik Asap Cerutu’ - Intan Dwi Hardiyati; Efi Fadilah; Heru Rianto Budian (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
Shooting in a video feature requires the right cinematographic strategy to build emotional closeness between the audience and the subject. The creation of “Perempuan di Balik Asap Cerutu” raises the story of female cigar-rolling workers using a cinematographic approach that emphasizes close-up and handheld techniques. The close-up technique is used to create emotional intimacy through detailed expressions and the subject’s activities, while the handheld technique gives a spontaneous and realistic impression, as if the audience is present in the event. This work aims to build an emotional connection between the audience and the subject, thus evoking empathy and public concern for the fate of female workers in Indonesia. Through a work that delivers a story capable of stirring emotions, it also highlights the lives of working women who are rarely represented in the media. The production process is divided into three stages: pre-production (research, observation, concept development), production (shooting using cinematographic techniques), and post-production (footage selection and audio-visual editing). The use of close-up and handheld techniques not only functions aesthetically, but also reflects the creator’s empathetic attitude toward the subject (ethical), and supports a more touching and human narrative delivery (narrative).